Proton Pump Inhibitors in the COVID-19 Pandemic - T. E. Kugler; I. S. Malovichko; V. B. Gnilitskaya; A. L. Khristulenko; N. F. Yarovaya (Архивъ внутренней медицины)
The safety of proton pump inhibitors (PPIs) use in coronavirus infection (COVID-19) is not well understood. PPIs are potent suppressors of gastric secretion and become one of the ten most widely used drugs in the world. They are expected to influence virus susceptibility, severity, and outcomes in patients diagnosed with COVID-19. This concern is based on their mechanism of action — suppression of gastric acidity, which is considered the first line of defense against infections. Taken together, the results of most studies and meta-analyses support that PPIs use has been associated with increased risk of COVID-19 and severe outcomes. However, taking into account all potential risk factors for disease severity seems impossible in the real world in the context of COVID-19, so conclusions about causal relationships between PPI use and COVID-19 should be treated with great caution. An additional interesting point about the use of PPIs in the pandemic is that it reduced absorption of certain vitamins. On the other hand, several studies have appeared in the literature regarding the protective therapeutic effects of PPIs. There is growing evidence of an immunomodulatory and antifibrotic role of PPIs that could be used in the treatment of COVID-19. In addition, their ability to alkalize the contents of endosomes and lysosomes serves as an obstacle to the penetration of the virus into host cells. This review analyzes the possible effects of PPIs in patients with COVID-19.